The Influence of Communication, Conflict and Infrastructure on Teacher Performance at SMAN 2 Kota Sungai Penuh - Afrianti, Fitrina; Badriyah, Helni (The Future of Education Journal, 2024)
This research aims to find out: 1. To find out the influence of Communication on Teacher Performance at SMAN 2 Sungai Penuh partially and how big the influence is. 2. To find out the partial influence of conflict on teacher performance at SMAN 2 Sungai Penuh and how big the influence is. 3. To find out the partial influence of infrastructure on teacher performance at SMAN 2 Sungai Penuh and how big the influence is. 4. To find out the influence of Communication, Conflict and Infrastructure on Teacher Performance at SMAN 2 Sungai Penuh simultaneously and how big the influence is. The sampling technique in this research was carried out using saturated sampling. A total of 52 respondents. Data collection techniques use questionnaires and literature. The hypothesis of the research is Communication on Teacher Performance, this is proven by tcount > ttable (3.346 > 2.0106). Conflict on Teacher Performance is proven by t count > t table (9.305 < 2.0106). Infrastructure on teacher performance, this is proven by t count > t table (14,301> 2.0106) The results of the F test show that communication, conflict and infrastructure simultaneously influence teachers at SMAN 2 Kota Sungai Penuh. From the ANOVA test or F test, it turns out that F count was obtained (30,341 > 3.19).